|
|
(14 intermediate revisions by the same user not shown) |
Line 1: |
Line 1: |
− | ====Alternate check==== | + | ====Compute <math>q_y</math>==== |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | \mathbf{q} & = \begin{bmatrix} q_x \\ q_y \\ q_z \end{bmatrix} \\ |
| + | & = k \begin{bmatrix} \sin \theta_f \cos \alpha_f \\ \cos \theta_f \cos \alpha_f - 1 \\ \sin \alpha_f \end{bmatrix} |
| + | \end{alignat} |
| + | </math> |
| + | So: |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | \alpha_f & = \sin^{-1} \left[ \frac{q_z}{k} \right] \\ |
| + | \frac{q_x}{k} & = \sin \theta_f \cos \alpha_f \\ |
| + | \theta_f & = \sin^{-1} \left[ \frac{q_x}{k} \frac{1}{\cos \alpha_f} \right] \\ |
| + | \frac{q_y}{k} & = \cos \theta_f \cos \alpha_f - 1 \\ |
| + | q_y & = k \left ( \cos \left( \sin^{-1} \left[ \frac{q_x}{k} \frac{1}{\cos \alpha_f} \right] \right ) \cos \left ( \sin^{-1} \left[ \frac{q_z}{k} \right] \right ) - 1 \right )\\ |
| + | & = k \left ( \sqrt{ 1 - \left[ \frac{q_x}{k} \frac{1}{\cos \alpha_f} \right]^2 } \sqrt{ 1 - \left[ \frac{q_z}{k} \right]^2 } - 1 \right ) |
| + | \end{alignat} |
| + | </math> |
| + | Or equivalently: |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | q_y & = k \left ( \sqrt{ 1 - \left[ \frac{q_x}{k} \frac{1}{\sqrt{1-[q_z/k]^2}} \right]^2 } \sqrt{ 1 - \left[ \frac{q_z}{k} \right]^2 } - 1 \right ) \\ |
| + | & = k \sqrt{ 1 - \frac{q_x^2}{k^2 (1-q_z^2/k^2) } } \sqrt{ 1 - \frac{q_z^2}{k^2} } - k |
| + | \end{alignat} |
| + | </math> |
| + | |
| + | ====Scratch/working (contains errors)==== |
| As a check of these results, consider: | | As a check of these results, consider: |
| :<math> | | :<math> |
Latest revision as of 16:29, 15 April 2019
Compute 

So:
![{\displaystyle {\begin{alignedat}{2}\alpha _{f}&=\sin ^{-1}\left[{\frac {q_{z}}{k}}\right]\\{\frac {q_{x}}{k}}&=\sin \theta _{f}\cos \alpha _{f}\\\theta _{f}&=\sin ^{-1}\left[{\frac {q_{x}}{k}}{\frac {1}{\cos \alpha _{f}}}\right]\\{\frac {q_{y}}{k}}&=\cos \theta _{f}\cos \alpha _{f}-1\\q_{y}&=k\left(\cos \left(\sin ^{-1}\left[{\frac {q_{x}}{k}}{\frac {1}{\cos \alpha _{f}}}\right]\right)\cos \left(\sin ^{-1}\left[{\frac {q_{z}}{k}}\right]\right)-1\right)\\&=k\left({\sqrt {1-\left[{\frac {q_{x}}{k}}{\frac {1}{\cos \alpha _{f}}}\right]^{2}}}{\sqrt {1-\left[{\frac {q_{z}}{k}}\right]^{2}}}-1\right)\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/8f7e2abe145310960a6b1dde4005576e79712dd2)
Or equivalently:
![{\displaystyle {\begin{alignedat}{2}q_{y}&=k\left({\sqrt {1-\left[{\frac {q_{x}}{k}}{\frac {1}{\sqrt {1-[q_{z}/k]^{2}}}}\right]^{2}}}{\sqrt {1-\left[{\frac {q_{z}}{k}}\right]^{2}}}-1\right)\\&=k{\sqrt {1-{\frac {q_{x}^{2}}{k^{2}(1-q_{z}^{2}/k^{2})}}}}{\sqrt {1-{\frac {q_{z}^{2}}{k^{2}}}}}-k\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/5bd27521d100f3deff50504ebd028cb1df1d0710)
Scratch/working (contains errors)
As a check of these results, consider:

Where we used:
![{\displaystyle {\begin{alignedat}{2}\sin(\arctan[u])&={\frac {u}{\sqrt {1+u^{2}}}}\\\sin \theta _{f}&=\sin(\arctan[x/d])\\&={\frac {x/d}{\sqrt {1+(x/d)^{2}}}}\\&={\frac {x}{\sqrt {d^{2}+x^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/fc9628f0d308053600f4e02d8f80c69fc9f356d0)
And, we further note that:
![{\displaystyle {\begin{alignedat}{2}\cos(\arctan[u])&={\frac {1}{\sqrt {1+u^{2}}}}\\\cos \theta _{f}&={\frac {1}{\sqrt {1+(x/d)^{2}}}}\\&={\frac {d^{2}}{\sqrt {d^{2}+x^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/584da470743b7feac2b55988526dabce5b4313c4)
Continuing:
